HSP105 inhibition downregulates store-operated calcium entry and promotes acute UVB-induced tight junction disruption. - Kaiyi Zhou; Siyu Luo; Qinxiao Wang; Qian Ye; Sheng Fang (PLoS ONE)
Background Tight junction abnormalities are a common feature of inflammatory skin diseases such as psoriasis and atopic dermatitis and contribute to systemic immune responses. Evidence provided to date suggests that Heat shock protein 105 kDa (HSP105) exhibits significant protective effects in response to destructive external stimuli. However, its role in UV-induced skin tight junction remains to be fully understood. Objective To investigate the role and underlying mechanisms of HSP105 in acute UVB-induced tight junction damage. Methods By utilizing bioinformatics analysis, together with an in vitro UVB-induced tight junction injury model in HaCaT cells, we investigated the expression and localization of HSP105 and the tight junction proteins CLDN1, CLDN4, and OCLN. The role of HSP105 was further explored through shRNA-mediated silencing and lentiviral overexpression in HaCaT cells. Potential pathways by which HSP105 regulates tight junction were analyzed using the GSEA algorithm and validated through in vitro experiments. Results Acute UVB irradiation mainly disrupted the distribution of CLDN1, CLDN4, and OCLN in HaCaT cells, while gene expression remained largely unaffected. Acute UVB irradiation also caused a reduction in HSP105 protein levels in HaCaT cells. Inhibition of HSP105 expression worsened tight junction fragmentation. GSEA analysis showed that Store-operated calcium entry (SOCE) was significantly correlated with HSP105 expression. Silencing HSP105 downregulated STIM1 transcription and inhibited SOCE, leading to further fragmentation of tight junction proteins. Overexpression of HSP105 partially mitigated the damage to tight junction integrity caused by UVB and SOCE inhibition. Conclusion HSP105 protects against acute UVB-induced tight junction damage through the regulation of SOCE. Our findings offer new insights into the treatment of skin barrier injury.